Analysis of Optimization of Scan In and Out Goods Data Input Process to Increase Operational Efficiency at PT Indonesia Nippon Seiki - Muhammad Angga Anggriawan; Novi Handayani; Neneng Yuyu Yunida Husniawati (CV. Jala Berkat Abadi, 2026)
This study aims to analyze and optimize the process of data entry for goods using the scan in and scan out system at PT Indonesia Nippon Seiki. The research employs a descriptive method with a quantitative approach to describe the actual conditions and identify problems occurring in the warehouse data management process. Data collection techniques include observation, interviews, and documentation to obtain comprehensive, valid, and relevant data. The results show that the barcode-based data entry system implemented has improved the speed, orderliness, and accuracy of inventory data recording in a more systematic and integrated manner. However, several obstacles are still encountered in its implementation, such as delays in data input due to scanning queues, barcode reading errors, discrepancies between system data and physical inventory, and network disruptions affecting real-time data access. These findings indicate that system effectiveness is not solely determined by technology but is also influenced by work procedures, human resource quality, and supporting infrastructure. Therefore, optimization efforts are required through workflow improvements, employee competency enhancement, network system strengthening, and the implementation of more effective and sustainable internal controls to improve the company’s operational performance.